DETERMINANTS OF BANKING PERFORMANCE IN INDONESIA: A HUMAN CAPITAL PERSPECTIVE - Suwinto Johan; Claudia Gita Hapsari (Jurnal Manajemen, 2020)
The paper aims to study the determinants of banking performance from the human capital perspective. Banking is a service industry that heavily depends on human capital. Therefore, the research will focus on human capital quality in determining banking financial performance. This research analyses 5 ratios: Education Ratio, Average Age Ratio, Gender Composition, number of employees and number of branches. The dependent variable will be the profitability ratio represented by the return on asset (ROA). Linear regression is used to investigate the effect of human capital on banking performance. The software is the Statistical Program for Social Science (SPSS) software to test the research model. The samples are 11 banks which are categorized as Book 4 and Book 3 by the regulation of Bank Indonesia (the central bank of Indonesia). The data and financial performance are obtained from 2015-2018. The empirical results show that the human capital, particularly the total employees and total branch, has a significant influence on banking per-formance. All variables are significant at a <5%.